The Relation of Oxidative Stress and Hypercholesterolemia - Jarukamjorn, Kanokwan; Sinthorn, Wiladda; Pimson, Charinya (Thai Journal of Toxicology, 2020)
High cholesterol level has been correlated with lipid peroxidation and oxidative stress of vessels. Therefore, review on the relation of oxidative stress and hypercholesterolemia could bring supportive information for studying of the pathogenesis at molecular level in order to prevent or descend the imbalance of antioxidative system to diminish the incidence of hypercholesterolemia and/or incurrent complications. Oxidative stress is an imbalance between production of free radicals and antioxidative system in the body, resulted in damage of DNA, protein, and fat by lipid peroxidation process. Hypercholesterolemia is a metabolic disorder disease associated with behavior of high fat diet consumption, subsequently leading to high cholesterol in vessels which triggers free radical formation and decreases antioxidant capability. These have been implicated as a risk factor for complication symptoms such as hypertension, cardiovascular disease, or diabetes mellitus, etc.